ANALISIS Ã¢â‚¬Å“DISECONOMIES OF SCALEÃ¢â‚¬Â DAN DAYA SAING KAWASAN GERBANGKERTOSUSILA - Alkadri, Alkadri (Jurnal Sains dan Teknologi Indonesia, 2008)
During 2000-2005 period, Gerbangkertosusila Area (G-12 Area) in East Java Province has been growth rapidly. But, hypothetically, this area fall in diseconomies of scale and competitiveness decreasing at national level. Using the regional diseconomies of scale and regional competitiveness approachs, this paper analyzed the hypothetic of diseconomies of scale and competitiveness decreasing in G-12 Area. The result of analysis show that G-12 Area has been diseconomies of scale and competitiveness decreasing in many macroeconomic indicators, i.e. contribution of gross value added, income per capita, contribution of export, absorption of domestic and foreign investment, quantity of medium and large scale industries, and fiscal capacity.